Ocular Involvement as the Primary Presentation of Suspected Systemic Lupus Erythematosus: A Case of Bilateral Papilledema and Macular Edema - Junetta Airene Priskila Taba; Anak Agung Mas Putrawati Triningrat; Made Paramita Wijayati; I Made Agus Kusumadjaja (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease known for its varied clinical presentations, often affecting multiple organ systems. Ocular involvement is common in SLE, but posterior segment manifestations like papilledema are rare, occurring in only about 1% of SLE patients. This case report details a unique instance of bilateral papilledema and macular edema as the primary presentation of suspected SLE in a young female patient. Case presentation: A 24-year-old female presented with a one-week history of sudden-onset blurry vision in both eyes. Ophthalmological examination revealed reduced visual acuity (6/45 in both eyes), bilateral optic disc swelling, and macular edema. Further investigations, including Optical Coherence Tomography (OCT) and Magnetic Resonance Imaging (MRI), confirmed macular edema and optic nerve sheath distention. A positive Antinuclear Antibody (ANA) test suggested an autoimmune etiology. Lumbar puncture results were normal, ruling out idiopathic intracranial hypertension. The patient was diagnosed with bilateral papilledema and macular edema, with suspected underlying SLE. Prompt treatment with high-dose corticosteroids and acetazolamide led to significant clinical improvement. Conclusion: This case highlights the rarity of bilateral papilledema and macular edema as initial presenting features of suspected SLE. It emphasizes the importance of thorough ophthalmological examination and relevant investigations in patients with sudden vision loss. Early recognition of such rare presentations is crucial to prevent potentially sight-threatening complications. This case underscores the need for a multidisciplinary approach for accurate diagnosis and management of complex presentations of systemic autoimmune diseases.